Analisis Strategi Pemasaran Global Secara Segmentasi Targeting & Positioning Pada Mobil Listrik Build Your Dreams ( BYD ) - Daniel Christover Silaban, Wiltasar; Hafiy Prayitno, Muhammad (Shofanah Media Berkah, 2024)
The global automotive industry is experiencing development with the presence of cars or Electric Vehicles (EV). This development is driven by changes in technology, consumer preferences and market trends. Electric cars are considered a smart innovation for the automotive industry that cares about the environment. Build Your Dreams or known as BYD, is one example of an electric car automotive industry brand that is famous for its innovation in battery technology to new energy vehicles. Marketing strategy is key for BYD. The approach taken in the marketing strategy is by conducting Segmentation, Targeting, and Positioning (STP). This study aims to analyze the global marketing strategy by segmentation, targeting & positioning on the Build Your Dreams (BYD) electric car.